Planning for the Future: How ICT Professors Approach Retirement and Post-Career Life - Oliveira, João Paulo Couto De; Rocha, Larissa; Mendes, Fabiana Freitas; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Professors’ attitudes toward retirement vary widely, ranging from enthusiasm to reluctance. The retirement process of university professors in the field of Information and Communication Technology (ICT) presents a critical characteristic: ICT educators often work at the cutting edge of innovation, which may instill a strong drive to remain professionally engaged even after reaching traditional retirement age. Problem: The research problem focuses on understanding the factors that impact the retirement process of ICT professors in higher education. Solution: This study aims to investigate the human, organizational, legal, and regulatory factors that may affect the retirement process of ICT professors. IS Theory: This research is based on Contingency Theory, which emphasizes the need for organizations to adapt their practices to specific environmental conditions. Method: We conducted a survey with 176 ICT professors from various universities across the country to gather data on their perceptions and preparations for retirement. Summary of Results: Our findings reveal that most professors begin to consider retirement early (31.3%) or mid-career (21.6%). Over 64% plan to engage in leisure activities and travel after retirement, while continuing to contribute to academic research. Financial reserves and post-career activity planning are key aspects of this process. However, most universities do not offer training courses to prepare them for retirement. Contributions and Impact in IS: This study contributes to the Information Systems (IS) field by applying Contingency Theory to the development of guidelines that address the complex retirement process for ICT professors. This research also opens avenues for further studies on how IS frameworks can be applied to address transitions in professional life cycles, particularly in knowledge-driven fields like academia.